High‐dose chemotherapy followed by autologous peripheral blood stem cell transplantation for recurrent primary mediastinal malignant germ cell tumor: A case report. (28th December 2013) - Keino, Dai; Kondoh, Kensuke; Murata, Shunsuke; Ohyama, Ryo; Morimoto, Mizuho; Muto, Shinji; Fukuda, Miho; Wakisaka, Munechika; Kitagawa, Hiroaki; Kinoshita, Akitoshi
Abstract A 15‐yr‐old boy presented with an anterior mediastinal mass, multiple lung metastases and obstruction of the left brachiocephalic vein, the superior vena cava and the subclavian vein. Tumor biopsy by CT guidance confirmed a diagnosis of GCT. Five courses of BEP therapy were performed, and CT of the chest revealed reduction in the anterior mediastinal mass and disappearance of the multiple lung metastases. We performed the anterior mediastinal mass extraction followed by adjuvant chemotherapy consisting of ICE and TIP. However, the AFP levels became elevated soon after. Abnormal accumulation was observed in the right upper lung by DW‐MRI. After the operation, two courses of TI chemotherapy and two courses of HDCT followed by auto‐PBSCT were performed. He was complicated with auditory disorder and renal dysfunction. Although HDCT followed by auto‐PBSCT was effective for the relapsed primary mediastinal GCT, a treatment strategy avoiding late complications is warranted.